Early‐age behavior and mechanical properties of cement‐based materials with various types and fineness of recycled powder. (30th June 2021) - Wu, Huixia; Liang, Chaofeng; Xiao, Jianzhuang; Xu, Jianguang; Ma, Zhiming
Abstract: Recycled powder (RP) that includes recycled paste powder (RPP), recycled mortar powder (RMP), and recycled concrete powder (RCP) is an eco‐friendly alternative binder. This work investigated the influence of RP types and fineness on early‐age behavior and mechanical strength of cement‐based materials. The results show that substituting RP for cement causes the reduction of new hydration products in cement‐based materials. The blended RP decreases the fluidity of paste mixture, and the fluidity of paste including fine RPP is lower than that of paste including fine RMP and RCP; moreover, the fluidity increases following the growth of RP particle size. Incorporating fine RPP shortens the setting time of cement‐based materials, while the setting time is prolonged as RMP and RCP incorporate; in addition, the enlarged particle size of RP prolongs the setting time. The drying shrinkage increases following the increasing replacement ratio of RPP. Incorporating less proportion of fine RMP and RCP lessens the drying shrinkage of paste, while the drying shrinkage increases after coarse or high‐volume RMP and RCP substituting. The maximum shrinkage of paste including 30% fine and coarse RCP is 3.4% and 7.3% higher than that of plain paste. Substituting fine RP for less dosage of cement has less impact on the mechanical strength of its newmade mortar, while the mechanical strength markedly decreases after high‐volume or coarse RP substituting. The compression strength of mortar including 30% fine and coarse RCP is 22.2% and 35.1% lower than that of plain mortar.